SOCIALLY STUDYING MUSIC AND MUSICAL SEMIOTICS. - G.Y. Yusupova (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article explores the social significance of music through the lens of musical semiotics. It discusses how music is not only a reflection of society but also a powerful force that shapes social experiences, identities, and power dynamics. While some theorists, such as Adorno, emphasize the autonomy of art, others argue for music's direct role in social interaction and political influence. The text critiques the limitations of traditional musicology and social sciences, which often neglect the meaning conveyed by sound itself. It calls for a deeper understanding of how musical sounds contribute to communication, identity, and social change.